Modeling PD Closed-loop Control Problems with Fuzzy Differential Equations. (1st October 2016) - Cazarez-Castro, Nohe R.; Cardenas-Maciel, Selene L.; Odreman-Vera, Mauricio; Valencia-Palomo, Guillermo; Leal-Ramrez, Cecilia
Abstract : This paper reports a fuzzy differential equations approach for the modeling of initial condition uncertainty for a proportional derivative closed-loop control of a direct current motor. Uncertainties are considered on the precision of the sensing devices installed on a driver. The closed-loop system is designed for a plant modeled with fuzzy differential equations. Satisfactory analytic and numerical results for the position regulation problem for ideal case and also considering perturbed initial conditions are reported.